1998
DOI: 10.1002/j.1550-8528.1998.tb00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Anthropometry and the Risk of Hip and Wrist Fractures in Men: Results from a Prospective Study

Abstract: Available epidemiological information on the associations between body anthropometry and the incidence of fractures in men is limited. We therefore prospectively investigated the association between body anthropometry and the incidence of hip and wrist fractures from low and moderate trauma among 43,053 men who were 40 years to 75 years of age in 1986 when they first enrolled in the Health Professionals Follow-Up Study. After 8 years of follow-up, 201 wrist fracture cases and 56 hip fracture cases were reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 55 publications
2
46
0
Order By: Relevance
“…This result may appear conflicting with several observations, arising from epidemiological studies and suggesting that a high BMI is protective against fractures. 9,[34][35][36] In these studies, it was proposed that BMI could provide: (1) skeletal loading, which may cause a compensatory increase in bone mass, [34][35][36] and (2) padding that protects against fractures during falls. 9 We do not want to argue against these potential benefits from a high BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may appear conflicting with several observations, arising from epidemiological studies and suggesting that a high BMI is protective against fractures. 9,[34][35][36] In these studies, it was proposed that BMI could provide: (1) skeletal loading, which may cause a compensatory increase in bone mass, [34][35][36] and (2) padding that protects against fractures during falls. 9 We do not want to argue against these potential benefits from a high BMI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Also there are evidences to suggest that an increased body fat mass decreases postural stability and increases the odds of falling, particularly when combined with low muscle mass. Owusu et al 9 reported that hip and wrist fractures among 43 053 men aged 40-75 years was increased depending on waist circumference and waist-tohip ratio. Four studies with obese boys also suggest that obesity imposes added constraints on the postural control system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked body shape with the risk of components of the metabolic syndrome (30 -32), as well as other health outcomes (33,34). A single 3-D body scan, repeated at intervals during adult life, may provide sensitive information about progression in risk and allow improved targeting of those most at risk.…”
Section: Discussionmentioning
confidence: 99%
“…(36) A small nested case-control study of men concluded there was no effect of abdominal fat, weight, or BMI on hip fracture risk. (37) However, results were presented only for linear associations among body size and adiposity variables, but as discussed above, those associations appear in fact to be nonlinear.…”
Section: Associations Between Bmi and Fracture Risk By Age And Sexmentioning
confidence: 99%